Impact of Extubation Time on Feeding Outcomes after Neonatal Cardiac Surgery: A Single-Center Study - Jeffrey W. Kepple; Meghan Kendall; Laura A. Ortmann (MDPI AG, 2023)
This study aimed to examine the impact of timing of extubation on feeding outcomes in neonates after surgery for congenital heart disease. This was a single-center retrospective study between December 2014 and June 2020. Patients were divided into three categories: extubated in the OR (immediate), extubated in the intensive care unit (ICU) between 0 and 3 days post-procedure (early), and extubated >3 days post-procedure (delayed). Comparing the immediate and early groups, we found no difference in time to first enteral feed (1.3 days (1.0-3.4) vs. 2.3 days (1.1-3.3), p = 0.27). There was no difference in time to first oral feed (2.0 days (1.1-4.5) vs. 3.1 days (1.8-4.4), p = 0.34) and time to goal feed (6.0 days (3.2-8.3) vs. 6.9 days (5.0-9.0), p = 0.15)). There was no difference in all oral feeds at one year: 88% vs. 98%, p = 0.16. The delayed extubation group performed significantly worse on all measures. Immediate and early extubation displayed no differences in feeding outcomes and length of stay in this study, while delayed extubation performed worse on all measures. Thus, we believe that clinicians should emphasize extubation within 3 days post-surgery to improve feeding outcomes while minimizing time hospitalized.